Association between methionine sulfoxide and risk of moyamoya disease - Li, Junsheng; Ge, Peicong; He, Qiheng; Liu, Chenglong; Zeng, Chaofan; Tao, Chuming; Zhai, Yuanren; Wang, Jia; Zhang, Qian; Wang, Rong; Zhang, Yan; Zhang, Dong; et al. (Frontiers in Neuroscience, 2023)
Objective: Methionine sulfoxide (MetO) has been identified as a risk factor for vascular diseases and was considered as an important indicator of oxidative stress. However, the effects of MetO and its association with moyamoya disease (MMD) remained unclear. Therefore, we performed this study to evaluate the association between serum MetO levels and the risk of MMD and its subtypes. Methods: We eventually included consecutive 353 MMD patients and 88 healthy controls (HCs) with complete data from September 2020 to December 2021 in our analyses. Serum levels of MetO were quantified using liquid chromatography-mass spectrometry (LC-MS) analysis. We evaluated the role of MetO in MMD using logistic regression models and confirmed by receiver-operating characteristic (ROC) curves and area under curve (AUC) values. Results: We found that the levels of MetO were significantly higher in MMD and its subtypes than in HCs (P<0.001 for all). After adjusting for traditional risk factors, serum MetO levels were significantly associated with the risk of MMD and its subtypes (P<0.001 for all). We further divided the MetO levels into low and high groups, and the high MetO level was significantly associated with the risk of MMD and its subtypes (P<0.05 for all). When MetO levels were assessed as quartiles, we found that the third (Q3) and fourth (Q4) MetO quartiles had a significantly increased risk of MMD compared with the lowest quartile (Q3, OR: 2.323, 95%CI: 1.088-4.959, P=0.029; Q4, OR: 5.559, 95%CI: 2.088-14.805, P=0.001). Conclusion: In this study, we found that a high level of serum MetO was associated with an increased risk of MMD and its subtypes. Our study raised a novel perspective on the pathogenesis of MMD and suggested potential therapeutic targets.